An annotated checklist of the Iranian Brentidae (Coleoptera: Curculionoidea) - Ghahari, Hassan; Colonnelli, Enzo (Zootaxa, 2020)
An annotated synopsis of Iranian Brentidae (Coleoptera: Curculionoidea) is provided as a basis for future studies, with notes on distribution and plant associations. In total, 123 species from 41 genera and 3 subfamilies, Apioninae (109 species within 32 genera), Brentinae (3 species within 3 genera) and Nanophyinae (11 species within 6 genera) are listed. Six species, Allomalia setulosa (Tournier, 1869), Corimalia fausti fausti (Reitter, 1890), Melanapion (Rhodapion) hauseri (Wagner, 1906), Protapion assimile assimile (Kirby, 1808), Pseudoperapion brevirostre (Herbst, 1797) and Titanomalia komaroffi (Faust, 1877) are new records for the fauna of Iran.